Intellectual capital in rehabilitation organizations: Concept clarification - Nikta Hatamizadeh; Mohammad Ahmadi; Roshanak Vameghi; Mohammad Ali Hosseini (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This paper aims to clear ambiguities regarding the definition of intellectual capital and its components in the evaluation of rehabilitation organizations. Design/methodology/approach - A preliminary definition of intellectual capital and its three domains of human, relational and structural capital and separate lists of proposed components for each domain was developed based on the results of a previous study. Fourteen experts in rehabilitation, health management and management engaged in Delphi rounds to reach agreed-upon definitions. Their ideas on relevance and the measurements of each proposed component in the assessment of intellectual capital in rehabilitation organizations were gathered by a questionnaire. Findings - Intellectual capital was defined as "The capital that emerges from the interaction of human resources' 'ability to think' and to 'create ideas' with 'a favorable internal and external organizational environment' (including the managerial, social, structural, and physical environment, as well as communication between the inside and outside of the organization)." This capital is expected to gradually increase with further education, skills training and the gaining of experience by staff and managers. Also, the further development of intra-organizational structures and inter-relations with the market will empower the organization to adapt to continually changing circumstances, leading to competitive value and profit. Finally, a list of 101 proposed components was agreed upon in the evaluation of intellectual capital in rehabilitation organizations. Originality/value - This paper may lead to the development of measurement tools and ultimately to planning effective programs to increase intellectual capital in rehabilitation organizations.